This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We see that c o s ( 1 0 3 π − 2 x ) = 0 is not the solution, so now with c o s ( 1 0 3 π − 2 x ) = 0 ⇔ x = 5 − 2 π + k 2 π ( k ∈ Z ) , we multiply both side with it and get s i n ( 5 3 π − x ) = s i n ( 1 0 π + 2 3 x ) c o s ( 1 0 3 π − 2 x ) ⇔ s i n ( 5 3 π − x ) = 2 1 [ s i n ( 5 2 π + x ) + s i n ( 2 x − 5 π ) ] Set x + 5 2 π = t and we get s i n ( π − t ) = 2 1 [ s i n ( t ) + s i n ( 2 t − π ) ] The equation above gives us s i n ( t ) = 0 and c o s ( t ) = 2 − 1 . Solve them and we have x = { 5 − 2 π + k π ; 1 5 4 π + k 2 π ; 1 5 − 1 6 π + k 2 π ∣ k ∈ Z } . Due to the condition, we'll have x = { 5 3 π + k 2 π ; 1 5 4 π + k 2 π ; 1 5 − 1 6 π + k 2 π ∣ k ∈ Z } Since x ∈ [ − π ; π ] , we'll get 3 roots x = { 5 3 π ; 1 5 4 π ; 1 5 1 4 π }